2009
DOI: 10.1111/j.1471-0528.2009.02209.x
|View full text |Cite
|
Sign up to set email alerts
|

Priorities in emergency obstetric care in Bolivia––maternal mortality and near‐miss morbidity in metropolitan La Paz

Abstract: Objective To document the frequency and causes of maternal mortality and severe (near-miss) morbidity in metropolitan La Paz, Bolivia.Design Facility-based cross-sectional study.Setting Four maternity hospitals in La Paz and El Alto, Bolivia, where free maternal health care is provided through a government-subsidised programme.Population All maternal deaths and women with near-miss morbidity.Methods Inclusion of near-miss using clinical and managementbased criteria.Main outcome measures Maternal mortality rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 23 publications
4
31
0
1
Order By: Relevance
“…However, a study conducted in urban setting in Bolivia where there are several maternity hospitals and located in short distance found that majority of near miss cases arrived in critical condition [18]. It is quite obvious that the main obstacle to arrive timely is not a physical barrier like transportation but more towards nonphysical barriers.…”
Section: Delayed Decision To Seek Care (Phase 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, a study conducted in urban setting in Bolivia where there are several maternity hospitals and located in short distance found that majority of near miss cases arrived in critical condition [18]. It is quite obvious that the main obstacle to arrive timely is not a physical barrier like transportation but more towards nonphysical barriers.…”
Section: Delayed Decision To Seek Care (Phase 1)mentioning
confidence: 99%
“…Many recent studies found that third delay is significantly associated with a higher risk of developing severe maternal morbidity [26][27][28][29]. They found that majority of the patients arrived at the referral health facility in a critical condition or severe complication which indicates barriers to reach the treatment [15,18].…”
Section: Delayed Provision Of Adequate Care (Phase 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…31 Phase III The cumulative effect of phase I and II delays contributes to the number of women reaching facilities in a serious condition. 25,34,36 Many will never reach a hospital, 22,33 and even when they do, treatment may not be successful.…”
Section: Phase IImentioning
confidence: 99%
“…maternal morbidity which has remained largely undescribed. In 2009, Roost et al [2] reported MMR as 187/100,000 LB and MNM as 50/1,000 LB, with a relatively low mortality index (MI) of 3.6 %.…”
Section: Introductionmentioning
confidence: 99%